Curating a Cybersecurity CV that Shines. (24th December 2020) - Lee, Rob
Abstract: While lockdown has decimated many of our industries, causing redundancies and insolvency for many, Rob Lee MBCS CISSP, explains how the new normal can be an opportunity to upgrade your CV and video interview technique.